Children's quest for love and professional child protection work: the case of Norway. Issue 1 (1st December 2016) - Neumann, Cecilie Basberg
Abstract : Central actors in the child protection field in Norway argue that children in public care should not only receive care and support, but also love. It is hard to disagree that children need love. However, there is reason to question the situation that may arise if children's need for love is translated into requirements that must be safeguarded and handled by child protection workers in the child protection services. In this article, I analyse this 'requirement of love' both with regard to the increased focus on children's rights in discussions on children's life conditions and to the history of the professionalisation of social work; having the gendered features of social work and its partial professionalisation in mind. Due to the challenges this requirement represents, there may be good reasons to revisit the debates on care and care work among feminists who have theorised care as work within professional contexts. I try to show how the field of social work and child protection may utilise the critical potential in care feminist thinking by connecting it to their own emphasis on emotional awareness and knowledge of self as a prerequisite for professional child protection work.